21. Pułk Piechoty von Borcke (4. Pomorski) w bitwie pod Bolimowem w świetle badań archeologicznych - Natkański, Karol E.; Świątkiewicz, Piotr (Acta Universitatis Lodziensis. Folia Archaeologica, 2018)
The article narrated mainly the results of the archaeological research carried out in the little town Bolimów, Pl. 9 (St. 9) in 2005 and village Joachimów-Mogiły Pl. 1 (St. 1) in 2008, on the newly built route of the highway A no. 2, (near Skierniewice in Central Poland). The results of the surveys have been limited only to the threads relating to World War I. At the same time, this article is an attempt to bind the information obtained during the test from the message history published in 1931 in the form of memories, providing a description of the combat route 21. Inf. Regiment called von Borcke at Thorn (Toruń). This unit from mid-February to mid-May 1915, stayed near the city of Bolimów. The battalions fighting directly on the front lines, occupied the positions in the trenches in the vicinity of the village Humin, to the east of the river Rawka. Other subunits were lodged in the camp called “Reserve-Lager”. This Reserve-Lager is located, according to the guidelines contained in the publication, on the southern edge of Bolimów, on the western riwer bank of Rawka. In this place, in the course of archaeological research carried out on the route of the highway A no. 2, some traces of fortifications (trench and shelter) and remains of German soldiers from the war were discovered. Some paper monuments allow to bind them with Toruń 21. Inf. Regiment. At the same time, on the opposite bank of the Rawka, in the village of Joachimów-Mogiły, some fragments of trenches as well as a hidden access to the ford on the Rawka and to Resereve-Lager were recorded. The material presented in the article is a hypothetical thesis complemented by knowledge of modern battlefields. Also, it provides a basis for the formulation of several author’s own comments for the discussion on the methodology of the emerging field of science that the archaeology of modern battlefields becomes.